Possible associations between anemia and gastric cancer - Pereira Alves, Nathália; de Paula Silva, José; Ribeiro Malta Neto, Natael; Paschoal de Souza, Yara; Belfort Piantino, Camila (O Mundo da Saúde, 2019)
Gastric cancer has been affecting the Brazilian population, especially men and the population aged over 50 years old, and is therefore a relevant topic for promoting quality of life. This neoplasm may present comorbidities, creating obstacles in the patient's prognosis, such as anemia. Thus, herein, the analysis of the possible associations between anemia and gastric cancer, and the categorization tumor staging, histological type, location, gender, age, leukogram and cause of death of patients with gastric cancer treated at the Regional Cancer Hospital (HRC) of Passos- MG, from January 2012 to December 2014, was proposed. This was a cross-sectional observational study with data obtained from documentary sources. The results from the analysis of 78 medical records showed that 69.23% of the patients are men and the predominant age range was between 70 and 80 years (32.04%). The gastric antrum was the most recurrent location of primary tumors (26.92%) and the prevalent histological type was adenocarcinoma (66.67%). Regarding tumor staging, T3, N0, M0 was observed in 23.07% of the cases. Regarding the mortality rate, it was observed that 64.1% of the deaths resulted from cancer. Meanwhile, for the hemogram, 61% anemia was observed, and all presented normal values when the leukogram was analyzed. It is concluded that the majority of gastric cancer patients had anemia, were male, predominantly aged between 70 and 80 years, with adenocarcinoma being the most prevalent type of tumor and gastric antrum being the most affected anatomical region.